Morfem Terikat Bahasa Melayu Riau Dialek Tanjung Balai Karimun - Siti Kartika (Madah: Jurnal Bahasa dan Sastra, 2021)
This study discusses the types and grammatical meanings of the morpheme bound to the Riau Malay language, Tanjung Balai Karimun dialect. This study uses a qualitative approach and descriptive method which aims to describe the type of bound morpheme of the Riau Malay language in the Tanjung Balai Karimun dialect and to describe the grammatical meaning of the bound morpheme in the Riau Malay language in the Tanjung Balai Karimun dialect. The object of this research is the Riau Malay language utterance in the Tanjung Balai Karimun dialect used by the people of Tanjung Balai Karimun. Data obtained by fishing techniques, interview techniques, and recording techniques, identified into the form and meaning of the bound morpheme, classified data based on the form and meaning of the bound morpheme and analyzed based on the form and meaning of the bound morpheme in the Riau Malay language, Tanjung Balai Karimun dialect. Morpheme is tied to the Riau Malay language, the Tanjung Balai Karimun dialect, which is then formulated into a conclusion. Based on classifying and analyzing the data, it was concluded that there were five types of bound morphemes, namely: prefix, infix, suffix, confix, and symulfix. The total number of data on the morpheme bound to the Riau Malay language, Tanjung Balai Karimun dialect is one hundred and twenty four.